Analisis Peran Penggunaan Aplikasi TikTok Edu dan Peran Partisipatif Siswa terhadap Kemampuan Akademik Siswa pada Masa Kurikulum Merdeka: Analysis of the Role of Using the TikTok Edu Application and the Participatory Role of Students on Students' Academic Abilities during the Independent Curriculum Period - Arman Paramansyah; Ulfah Sa'adah; Rahmawaty Parman; Tuti Puspitasari; Basuki Wisnu; Jeditia Taliak (ITScience (Information Technology and Science), 2024)
One form of implementation of technology and digitalization in education is integrating social media sites such as TikTok Edu into the education curriculum. In addition to functioning as entertainment, this software provides students with an engaging and dynamic learning tool. The purpose of this study was to analyze how the use of the TikTok Edu application and the participatory role of students contribute to improving their academic abilities in the context of the Independent Curriculum. With a survey methodology involving 200 students, this study used quantitative techniques. Using a multiple linear regression approach, the survey measured how much students utilize TikTok Edu and actively participate in education. The study results show that using the TikTok Edu application significantly improves students' understanding of academic material because this platform provides a more interactive, interesting learning method based on students' learning styles in the digital era. Students' active participation in learning through online discussions, collaboration in creating educational content, or reflection on the material presented also improves their understanding and academic achievement. Based on these findings, the study recommends the broader use of TikTok Edu in the world of education as a supporting tool in the implementation of the Independent Curriculum, which emphasizes student independence in determining the most effective way of learning for them, increasing creativity in absorbing and conveying information, and encouraging active participation in various learning activities.